Bottlenecks for Evidence Adoption - DellaVigna, Stefano; Kim, Woojin; Linos, Elizabeth (Journal of Political Economy, 2024)
Governments increasingly use RCTs to test innovations, yet we know little about how they incorporate results into policy-making. We study 30 U.S. cities that ran 73 RCTs with a national Nudge Unit. Cities adopt a nudge treatment into their communications in 27% of the cases. We find that the strength of the evidence and key city features do not strongly predict adoption; instead, the largest predictor is whether the RCT was implemented using pre-existing communication, as opposed to new communication. We identify organizational inertia as a leading explanation: changes to pre-existing infrastructure are more naturally folded into subsequent processes.